Existence of positive solutions for the fractional q-difference boundary value problem - Yue Liang; He Yang; Hong Li (Advances in Difference Equations, 2020)
Abstract In this paper, we investigate the existence of positive solutions for a class of fractional boundary value problems involving q-difference. By using the fixed point theorem of cone mappings, two existence results are obtained. Examples are given to illustrate the abstract results.